Deficit Subsurface Drip Irrigation Improves Water Use Efficiency and Stabilizes Yield by Enhancing Subsoil Water Extraction in Winter Wheat - Yang, Ming-Da; Leghari, Shah Jahan; Guan, Xiao-Kang; Ma, Shou-Chen; Ding, Chao-Ming; Mei, Fu-Jian; Wei, Li; Wang, Tong-Chao (Frontiers in Plant Science, 2020)
Understanding the temporal and spatial patterns of soil water extraction and their impacts on growth response of winter wheat to deficit subsurface drip irrigation (SDI) conditions is critical for managing water scarcity and stabilizing yield. A field experiment was conducted from 2016 to 2018 involving five SDI amounts: 0.25 ETc, 0.4 ETc, 0.6 ETc, 0.8 ETc, and 1.0 ETc, representing 25%, 40%, 60%, 80%, and 100% of crop evapotranspiration (ETc), respectively. The results showed that the 0.6 ETc treatment significantly increased soil water extraction from 40–80-cm and 80–140-cm from jointing to maturity as compared to the 1.0 ETc treatment. Whereas the 0.8 ETc treatment significantly increased soil water extraction from 80–140-cm deep soil from flowering to maturity in the first growing season. The crop was most water-stressed under the 0.25 ETc and 0.4 ETc treatments, thus extracted more soil water from 0–140-cm soil profile. However, both treatments exhibited minimum plant tillers, lowest leaf water content, leaf area index (LAI), photosynthetic rate (Pn), and transpiration rate (Tr) as well as grain yield. All these parameters, except for leaf water content, Pn after the flowering stage, and grain productivity, were also reduced in the 0.6 ETc treatment than the 1.0 ETc treatment. The differences between the 0.8 ETc and 1.0 ETc treatments were minor in terms of plant height, LAI, spike number, Pn and Tr, but infertile tillers were fewer in the 0.8 ETc treatment. We obtained high yield from the 0.8 ETc treatment, and the 0.6ETc treatment resulted in the highest harvest index with improved WUE than other treatments. Integrating deficit irrigation into SDI can save water in winter wheat production in water-limited regions, which can not only enhance soil water extraction from deep soil layers, but also sustained yield by stimulating crop growth. Therefore, a deficit SDI system would be used to conserve water in water-limited regions.